2020
DOI: 10.1086/710975
|View full text |Cite
|
Sign up to set email alerts
|

Declining Search Frictions, Unemployment, and Growth

Abstract: Over the last century, unemployment, vacancy, job-finding and job-loss rates as well as the Beveridge curve have no trend. Yet, the last century has seen the development and diffusion of many information technologies-such as telephones, fax machines, computers, the Internet-which presumably have increased the efficiency of search in the labor market. We explain this phenomenon using a textbook search-theoretic model of the labor market. We show that there exists an equilibrium in which unemployment, vacancies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Although the interaction of these cost reductions is not unambiguous (see e.g. Albrecht et al (2006)), there is some evidence of increases in matching efficiency (Martellini and Menzio, 2020). We therefore use broadband penetration as a proxy for E as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the interaction of these cost reductions is not unambiguous (see e.g. Albrecht et al (2006)), there is some evidence of increases in matching efficiency (Martellini and Menzio, 2020). We therefore use broadband penetration as a proxy for E as well.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, our model offers a new perspective on the puzzle identified by Martellini and Menzio (2020). They wonder why unemployment does not show a trend despite apparent improvements in labour market efficiency.…”
Section: Proofmentioning
confidence: 91%
See 1 more Smart Citation
“…The possibility that efficiency gains are showing up in price increases due to higher quality matches is a broader issue that applies to all search markets, not just housing. Martellini and Menzio (2018) argue that this may explain why the labor market has not experienced significant declines in job vacancy and unemployment rates despite known technological improvements in job search. Martellini and Menzio (2018) showed that if the match quality distribution is Pareto, then unemployment, job vacancy, job-finding, and job-loss rates remain constant even as the efficiency of search grows over time.…”
Section: Implications For Economic Growth and Productivitymentioning
confidence: 99%
“…Martellini and Menzio (2018) argue that this may explain why the labor market has not experienced significant declines in job vacancy and unemployment rates despite known technological improvements in job search. Martellini and Menzio (2018) showed that if the match quality distribution is Pareto, then unemployment, job vacancy, job-finding, and job-loss rates remain constant even as the efficiency of search grows over time. Improvements in search technology show up in productivity growth.…”
Section: Implications For Economic Growth and Productivitymentioning
confidence: 99%